2017
DOI: 10.1038/s41598-017-06732-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in ERCC1 confers susceptibility of coronary artery disease and severity of coronary artery atherosclerosis in a Chinese Han population

Abstract: Excision repair cross-complementing 1 (ERCC1) gene encodes ERCC1 protein, which is mainly responsible for the repair of DNA damage in different diseases including coronary artery atherosclerosis by acting as a rate-limiting element in nucleotide excision repair (NER). Using a three-stage case-control study with 3037 coronary artery disease (CAD) patients and 3002 controls, we investigated associations of three single nucleotide polymorphisms (SNPs) with CAD risk and severity of coronary artery atherosclerosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…There is at least one single nucleotide polymorphism in ERCC1 significantly associated with coronary artery disease (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is at least one single nucleotide polymorphism in ERCC1 significantly associated with coronary artery disease (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of the DNA repair proteins PCNA, DNA‐PKcs, and APE1 is correlated with left ventricular dysfunction in patients with idiopathic dilated cardiomyopathy, suggesting increased DNA repair activity in diseased cardiac tissue (Bartunek et al, 2002 ). In contrast, reduced expression of numerous DNA repair genes, including ERCC1 , XPA , and ATM , are associated with stable angina and myocardial infarction (Zhang et al, 2017 ). There is at least one single nucleotide polymorphism in ERCC1 significantly associated with coronary artery disease (Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that A allele of the ERCC1 rs3212986 polymorphism might be a risk factor for ischemic stroke. The ERCC1 rs3212986 polymorphism, located on the 3'-UTR of the ERCC1 gene, has been widely studied in previous studies (16,22,23) and might be involved in the potential pathophysiological mechanism in ischemic stroke. ERCC1 rs3212986 polymorphism might affect the DNA repair capacity and interfere with the NER pathway by regulating ERCC1 transcription and translation and/or altering ERCC1 biological activity (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Aging has been associated with higher incidence of cardiac dysfunction; however, there are still unanswered questions about the exact molecular mechanisms driving this predisposition. In the past, Ercc1 deletion has been implicated with atherosclerotic cardiovascular disease both in mice (263) and in human patients (264). For this reason, we investigated whether systemic or mesenchymal-specific Ercc1 deletion causes any phenotype in the heart valves of Ercc1 Δ/or ColVI-Cre Ercc1 f/respectively and whether this deletion affects the heart valve disease developed in Tg197 mice.…”
Section: Discussion: Part IIImentioning
confidence: 99%